Dilemas e desafios da proteção social especial no âmbito do suas: uma contribuição ao debate - Duarte, Joana Maria Gouveia Franco (2012)
This dissertation object of study is the Special Social Protection (PSE) and some of its dilemmas and challenges in the contemporary reconfiguration of social assistance policy in Brazil. The general objective aimed to deepen theory on issues surrounding the PSE and to offer subsidies for reflection, discussion and action strategies to employees of the SUAS to put in effect, in order to achieve the critical perspective of Social Service in the contemporary ethnical project. The driving question of such study was the definition of what are the current dilemmas and challenges to PSE and how one can improve quality of attention to violation of rights and risks observed in the National Social Police Plan (PNAS). The main conceptual references were based on works and authors that emphasize critical perspective. The methodology included a literature review, documental research and empirical approach to the research subjects, and participant observation, since the author of this dissertation coordinates a Special Social Protection in the city of Diadema. The study focused on defining the PSE area of action and the ambience of PNAS rights violation that characterizes it, defining the path that led to PSE and shedding light contemporary issues such as: requirements for the new thinking in PSE; the multiple determinants of Specialized Care and Protection of Families and Individuals (PAEFI); current requirements for PSE professionals; the National Grading of Social Services; the interface with Law and the expression of conservative ideas by some PSE care providers The subjects of this study were: social service workers, psychologists and educators, all employees of SUAS. The main conceptualreferences were: Social Policy, Social Assistance, Social Protection in Brazil and Social Rights, Social Aid Rights, Social Security. The research confirmed the hypothesis of the need to go deeper on issues related to PSE through durable qualification processes in order to understand and lead this process of reordering PSE